Quantum-state-controlled channel branching in cold Ne(3P2)+Ar chemi-ionization. Issue 12 (December 2018) - Gordon, Sean; Omiste, Juan; Zou, Junwen; Tanteri, Silvia; Brumer, Paul; Osterwalder, Andreas
Abstract A prerequisite to gain a complete understanding of the most basic aspects of chemical reactions is the ability to perform experiments with complete control over the reactant degrees of freedom. By controlling these, details of a reaction mechanism can be investigated and ultimately manipulated. Here, we present a study of chemi-ionization—a fundamental energy-transfer reaction—under completely controlled conditions. The collision energy of the reagents was tuned from 0.02 K to 1, 000 K, with the orientation of the excited Ne atom relative to Ar fully specified by an external magnetic field. Chemi-ionization of Ne(3 P2 ) and Ar in these conditions enables a detailed investigation of how the reaction proceeds, and provides us with a means to control the branching ratio between the two possible reaction outcomes. The merged-beam experimental technique used here allows access to a low-energy regime in which the atoms dynamically reorient into a favourable configuration for reaction, irrespective of their initial orientations. Steric effects in a fundamental energy-transfer reaction at collision energies from over 1, 000 K down to 20 mK have now been studied. At high energies a pronounced dependence of the reactivity on the reactant orientation is observed, but this effect is not present at the lowest energies because of dynamic reorientation.